PEMERIKSAAN KADAR GLUKOSA DARAH SEWAKTU PADA PASIEN GAGAL GINJAL RONIK SETELAH HEMODIALISA - Eli Yusrita; Elvanza Natasyah; Mega Elfia (Ensiklopedia Research and Community Service Review, 2026)
Chronic kidney disease (CKD) is a progressive and irreversible impairment of kidney function that disrupts fluid and electrolyte balance in the body. One of the renal replacement therapies for is hemodialysis. However, this procedure may lead to metabolic complications, including alterations in blood glucose levels, both in diabetic and non-diabetic patients. This study aimed to determine the profile of random blood glucose levels in Chronic kidney disease patients after undergoing hemodialysis. This descriptive study used a cross-sectional approach and was conducted at Harmoni Laboratory, Pekanbaru, in March 2025. A total of 30 were selected using sampling. Blood glucose levels were measured using the Glucose Oxidase-Peroxidase Aminoantipyrine Phenol (GOD-PAP) method. The results showed that 7 respondents (23.3%) had low glucose levels, 6 respondents (20%) had high levels, and 17 respondents (56.7%) had normal glucose levels. The average random blood glucose level was 116.1 mg/dL. Age and gender influenced glucose levels, with the majority of abnormal values found in male patients and those aged 41–70 years. In conclusion, most CKD patients after hemodialysis had random blood glucose levels within the normal range, although some exhibited low or high levels.Keywords: Random Blood Glucose, Chronic Kidney Disease, Hemodialysis